Porous friction layer as a sustainable urban drainage strategy: Technical and economic feasibility for Governador Valadares – Minas Gerais - Brazil (Research, Society and Development, 2026)
The overall objective of this research is to evaluate, based on a specialized literature review, the technical and economic feasibility of the Porous Friction Layer (PFL) as a sustainable urban drainage solution for the municipality of Governador Valadares, MG, considering its potential hydrological, environmental, regulatory, and operational benefits.The research integrates recent scientific studies, such as GIS and pedological approaches, that discuss the performance of PCFs in terms of reducing peak flows, improving stormwater quality, runoff, and drainage, as well as their contribution to mitigating heat islands in urban areas. The literature reviewed indicates that, although PCFs involve higher initial costs compared to conventional pavements, their medium- and long-term benefits include pollutant filtration, increased urban soil permeability, and strengthening green infrastructure. Studies also highlight the strategic role of PCFs in promoting water resilience and environmental sustainability in medium-sized cities. The conclusion is that PCFs constitute a promising alternative for public policies aimed at sustainable urban drainage and adaptation to climate change.